A review of cultural and ethnic bias in investigative decision-making: selected cases - Minhas, Rashid (Journal of ethnicity in criminal justice, 2023)
When making decisions, police, like all people, fall prey to negative stereotypes. Police must regularly make decisions about threats, so the stakes are higher than the typical decision-making process. This review looked at the threat and violence risk assessment processes through a new lens, exploring the relationship between (un)reasonable suspicion based on behaviors with an overreliance on perceived prejudicial stereotypes. The paper outlines seven cases exemplifying inaccurate assessment of threats based on two UK criminal justice policies, (i) stop and search; (ii) and the CONTEST strategy. The case analysis review suggests that assessments are based on unstructured judgments and profiling grounded in cultural, religious and racial stereotypes.